A rational design of an efficient counter electrode with the Co/Co1P1N3 atomic interface for promoting catalytic performance. (2nd March 2021) - Zhou, Danni; Xia, Zhaoming; Shang, Huishan; Xiao, Hai; Jiang, Zhuoli; Li, Haijing; Zheng, Lirong; Dong, Juncai; Chen, Wenxing
Abstract : The P, N co-stabilized cobalt single atom catalyst (Co/Co1 P1 N3 ) synthesized by in situ phosphatizing strategy was adopted as efficient counter electrode (CE) in dye-sensitized solar cells (DSSC), proven to be a brilliant candidate for traditional precious platinum (Pt) CE. Abstract : Interface engineering has been demonstrated to have a great effect on designing high performance catalysts. In particular, the interface design at the atomic scale is always a fortress to be overcome by researchers. Herein, we in situ introduced triphenylphosphine into cobalt atom sites in a metal–organic framework via encapsulation and successfully synthesized a cobalt single-atom catalyst with a co-coordinated atomic interface structure of P and N (Co/Co1 P1 N3 ). Adopted as a counter electrode (CE) in dye-sensitized solar cells (DSSCs), Co/Co1 P1 N3 demonstrates a power conversion efficiency (PCE) of 8.51%, outperforming Co/Co1 N4 (6.62%) counter electrode and commercial Pt (7.88%). We discover that the electron donation from the P dopant can reduce the electrostatic attraction between Co and I − ions, which favor I − desorption processes, sequentially boosting the activity of Co/Co1 P1 N3 .